Frederick J. Streng, Emptiness: A Study in Religious Meaning. A Depth Study of the Philosopher Nagarjuna and His Interpretation of Ultimate Reality. Nashville and New York, Abington Press, 1967. 252 pp. - C. W. Johnson G. C. (El Colegio de México, A.C., 1968)
-